Trajet?ria das pol?ticas educacionais e garantia do direito ? educa??o b?sica para estudantes com doen?a falciforme no munic?pio de Feira de Santana (1988 a 2016) - Santos, Gabriela Silva (2024)
The present work entitled "Trajectory of educational policies and guarantee of the right to basic education for students with sickle cell disease in the municipality of Feira de Santana (1988 to 2016)" is a master's thesis research that has as its object of study the educational policies that guarantee the right to education in Brazil. We seek to understand in this legislation what guarantees are guaranteed to people with Sickle Cell Disease (SCD). SCD is the chronic and hereditary disease with the highest incidence in Brazil, according to the Ministry of Health (2007). It is a health condition that brings several complications such as: necrosis of the extremity of the femur (the sphere of the ball joint of the hip, also called avascular necrosis), yellowing eyes, pain crises, among other symptoms. Morbidity and mortality and genetic variability are also a reality in SCD. While some people may have mild symptoms, others die. This understanding helps to realize that not all students with SCD will exhibit the same behavior at school. However, the scenario is one of lack of care and lack of adequate treatment in schools, which make the schooling process even more difficult for this public, contributing to the distancing of these people from school, causing age/year discrepancy and school dropout. In view of this, the studies were carried out with the following research question: What are the guarantees that educational policies present to ensure the right to basic education of students with SCD in Feira de Santana from 1988 to 2016? And as a general objective, to analyze what are the guarantees that the laws present to ensure the right to education of students with SCD in Feira de Santana. The specific objectives are: to analyze the legal constraints of public educational policies on the right to education of people with SCD as a health condition; analyze the guidelines of ANVISA's manual on FD; and, to identify how the educational legislation and its political-administrative conditions reverberate in the basic education of people with SCD in Feira de Santana ? BA. The study has a qualitative approach and to achieve the objectives, document analysis was used based on the studies of Cellard (2012) considering documents as a source of knowledge that enables historical knowledge. The documents selected for the analysis were: Federal Constitution of 1988, Statute of the Child and Adolescent of 1990, Law of Guidelines and Bases of Education LDB 9394/1996, National Education Plan (2014-2024), Law 13005/2014, School Health Program, State Education Plan of Bahia, Municipal Education Plan of Feira de Santana, Booklet entitled Sickle Cell Disease: Teacher's Manual of the Health Surveillance Agency (ANVISA) and Municipal Law 3412/2013. The selected documents are from different historical times, which also allows for a broader analysis. Together, the studies were carried out with emphasis on the power correlations of the different conceptions of the State and the impacts of neoliberalism on the right to education in the light of authors such as: Bobbio (1992), Gramsci (2007) and Dardot and Laval (2016). The results of the research indicate that the legal system silences the specificity of special needs for students who have SCD as a health condition. The study shows that the educational reality in Feira de Santana, through its guiding documents of education, has been following the same silence of the national scenario.